Land use and cropping pattern change in Chandauli district, Uttar Pradesh: A geographical analysis - Singh, Akhilesh Kumar; Singh, Arun Kumar (National Geographical Journal of India, 2022)
Observation of land uses is an important tool to assess surface change at different spatio-temporal scales. There are six categories of land use discussed in which agricultural land-use class one. Any plan or policy related to agriculture land use bringsa change in agricultural performance and cropping patterns. Apart from this, the cropping pattern is also governed by the law of comparative advantage concerning Agroclimatic conditions. The present paper focuses on the changes that have taken place in land use and cropping pattern in Chandauli district from 2000-01 to 2015-16. The study reveals that there has been a significant change in land use pattern and cropping pattern as settlement class of land use increase 22.72 per cent in 2015 and the area of rice and wheat crops increase 12829 ha. and 9767 ha. respectively from 2000-01 in the study area.